PTH-051 The First Years Outcome Data From Ibd-sshamp; Uk's First Remote Web-based Self Management Programme For Stable Inflammatory Bowel Disease Patients. (9th June 2014) - Johnson, MW; Lithgo, K; Price, T
Abstract : Introduction: In February 2012 the Luton and Dunstable University Hospital, became the first hospital in UK to use a remote (web-based) programme to help manage stable inflammatory bowel disease (IBD) patients. IBD-SSHAMP (Supported, Self Help And Management Programme) aimed to transfer the care of stable IBD patients from hospital based outpatient appointments (OPAs), to effective community based monitoring + management, co-ordinated by specialist IBD nurses. Objective: To improve cost efficiency by reducing the number of unnecessary routine OPAs + thereby improve OPA waiting times. Methods: The LandD manages 2420 active IBD patients, most of which are seen twice a year in routine OPAs. 26 lack mental capacity and 117 do not have internet access. Using Patient Knows Best we developed individualised websites for all of our IBD patients, to offer them a direct communication portal and a symptomatic assessment tool that provides appropriate management advice via a traffic light system. If a patient scores badly, an alert is sent out to the specialist team. The websites have a library of self help advice sheets and upload the patients hospital results in graphical form. The system can be converted into 6 different languages and has both iPhone or Android apps. Patients can access this service from the comfort of their own homes or (like a health passport) whilst on the move/abroad. A proportion of our more stable patients can be transferred to community based care via IBD-SSHAMP and receive twice yearly virtual (telephone) clinics with blood and faecal (calprotectin) inflammatory marker assessments. By freeing up OPA space we can accommodate emergency patients usually within 24–48 hrs. Results: We are steadily inviting the 2, 277 IBD patients who have internet access to a personalised website, and have successfully transferred 420 onto IBD-SSHAMP. We plan to transfer a further 400 to community based IBD-SSHAMP by the end of 2014. Confidence is such that this second wave will primarily contain patients stable on immunosuppressants eg. azathioprine. So far IBD-SSHAMP has saved our CCG approx £68, 000 (400 × 2 x £85), whilst reducing our OPA waiting times. Only 7 of our IBD-SSHAMP patients have required an emergency hospital OPA. We have received positive feedback from the patients, who feel more supported and appreciate that they are not being discharged. Conclusion: IBD-SSHAMP is the UK's first internet based remote management system for managing stable IBD patients. This proof of concept project, has proven to be effective, safe and cost efficient. Our CCG have fully supported the concept and outcome, funding 2 additional IBD nurses to support the system. The Regional CCG are now keen to roll this concept out through the East of England. Disclosure of Interest: None Declared.